PBRM1 (BAF180) protein is functionally regulated by p53‐induced protein degradation in renal cell carcinomas. Issue 4 (19th August 2015) - Macher‐Goeppinger, Stephan; Keith, Martina; Tagscherer, Katrin E; Singer, Stephan; Winkler, Juliane; Hofmann, Thomas G; Pahernik, Sascha; Duensing, Stefan; Hohenfellner, Markus; Kopitz, Juergen; Schirmacher, Peter; Roth, Wilfried
Abstract: About 40% of clear‐cell renal cell carcinomas (ccRCC) harbour mutations in Polybromo‐1 ( PBRM1 ), encoding the BAF180 subunit of a SWI/SNF chromatin remodelling complex. This qualifies PBRM1 as a major cancer gene in ccRCC. The PBRM1 protein alters chromatin structure and its known functions include transcriptional regulation by controlling the accessibility of DNA and influencing p53 transcriptional activity. Since little is known about the regulation of PBRM1, we studied possible mechanisms and interaction partners involved in the regulation of PBRM1 expression. Activation of p53 in RCC cells resulted in a marked decrease of PBRM1 protein levels. This effect was abolished by siRNA‐mediated down‐regulation of p53, and transcriptional activity was not crucial for p53‐dependent PBRM1 regulation. Pulse‐chase experiments determined post‐translational protein degradation to be the underlying mechanism for p53‐dependent PBRM1 regulation, which was accordingly inhibited by proteasome inhibitors. The effects of p53 activation on PBRM1 expression were confirmed in RCC tissue ex vivo . Our results demonstrate that PBRM1 is a target of p53‐induced proteasomal protein degradation and provide further evidence for the influence of PBRM1 on p53 function in RCC tumour cells. Considering the paramount role of p53 in carcinogenesis and the presumptive impact of PBRM1 in RCC development, this novel regulation mechanism might be therapeutically exploited in the future. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.